PENYUSUNAN ANALISIS JABATAN DAN ANALISIS BEBAN KERJA PADA SEKSI PENANGANAN FAKIR MISKIN PEDESAAN DI DINAS SOSIAL PROVINSI SULAWESI SELATAN - F. Tonapa, Jessica; Az-zahra Malik, Reinita (Politeknik STIA LAN Makassar, 2023)
There is an error in the job analysis and workload analysis at the South Sulawesi Provincial Social Service. Job analysis and workload analysis also still use the old format. Based on these problems, the study aims to improve job analysis and workload analysis through a design by the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 1 of 2020 in the Section for Handling the Rural Poor at the Social Service of South Sulawesi Province. The research method used in this study is qualitative. The data analysis method used is data reduction, data presentation, and data verification. The results of this study are job analysis and workload analysis containing 17 (seventeen) items of job information made based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 1 of 2020 concerning Guidelines for Job Analysis and Workload Analysis.